Pregnancy in a patient with dilated cardiomyopathy (DCM) - Aulia Mustika; Aruman Yudantho (Trends in Infection and Global Health, 2021)
Pregnancy in dilated cardiomyopathy (DCM) has an extremely high risk. However, DCM is usually asymptomatic at a young age. In pregnancy with DCM, it appears progressive and becomes symptomatic. and mimicking with peripartum cardiomyopathy (PPCM). We reported a case of a 23-year-old woman who was 20 weeks pregnant with her first child complained of chest palpitations and severe faintness. These progressive symptoms have happened and started during pregnancy. This case report suggests that physiological and emotional burdens are greater during pregnancy, especially for dilated cardiomyopathy (DCM) patients. This condition often leads to the progression of the DCM. The DCM often headways from the asymptomatic phase upturn to the symptomatic stage.